รูปแบบกลุ่มเครือข่ายคุรุศึกษาสาขาวิชาการศึกษาปฐมวัยของมหาวิทยาลัยสวนดุสิต - นิชานนท์ ผู้ช่วยศาสตราจารย์ ดร.ชนะศึก; ผลพันธิน รองศาสตราจารย์ ดร.ศิโรจน์; อุตภาพ ผู้ช่วยศาสตราจารย์ ดร.อารมณ์; อินทามระ อาจารย์พรรัก; รอดพ่วง อาจารย์ ดร.จิราพร; สมุทรเผ่าจินดา อาจารย์ประภาวรรณ; ติยะพงษ์ประพันธ์ นายวิชญา (Journal of Multidisciplinary in Social Sciences, 2017)
The model of the educational network in early childhood was developed based on the aims to examine the educational network model in Early Childhood Education, to give development guidelines to improve the educational network model in Early Childhood Education, and to provide guidance for personnel development for the Faculty of Education at Suan Dusit University. A qualitative methodology was applied by using data synthesis, interviews, and focus group discussions among academician and related sectors. The results revealed in three main areas: 1. The educational network model in Early Childhood Education of Suan Dusit University was formulated since the collaboration between Suan Dusit University and the Department of Local Administration in 2006 – 2008 based on the cooperation in Bachelor Degree curriculum management in early childhood educational programs. The managerial system for this program was divided in to two models, 1) the managerial model and 2) academic administration model. In the managerial model was specific for only this program and comprised the virtual university model and virtual organizational model. The virtual university model focused on three tools: Suan Dusit Internet Broadcasting (SDIB), Virtual Library, and Distance Learning. While virtual organizational model focused at the Content Management System (CMS). In terms of the academic administration model, it was found that the School-Based Teacher Education model, Work-Based Learning model and Tailor Made model were the most suitable for the students because they were all also full time teachers working in the child development center. Moreover, working under this program cultivated the early childhood educational network into three levels: 1) policy level, 2) organizational level, and 3) operational level. 2. The guidelines for the development of educational network model in Early Childhood Education, Suan Dusit University could be divided into two structures: management system structure and academic system structure. These two structures also helped to improve professionalism of teachers and administrators of Department of Local Administration. 3. The personnel development guidance for the Faculty of Education members of Suan Dusit University demonstrates that the faculty members were taught beneath this program in two parts: 1) the faculty members received three days (20 hours) of training in early childhood education, and 2) the faculty members can improve their teaching skills, Knowledge, profession skills, technology-based skills, teaching media development skills based on the local materials, and the integration of early childhood education and local wisdom.